PENGEMBANGAN BUDIDAYA IKAN HIAS DI DESA TONJONG KABUPATEN BOGOR - Panggabean, Donwill; Sapuriningsih, Chikita Lestari; Hotman, Jan; Saleha, Eha (Universitas Mataram, 2024)
The economy of local communities can be improved through the involvement of the community itself. Micro, small and medium enterprises (MSME) are one example. MSME are social institutions that function as a forum and means of development of every member of society, growing according to a sense of social responsibility from, for, and by the community. Community groups that are members of the